An empirical study on job prospects in BPO: Indian perspective - Dhermendra Mehta; Jitendra K. Sharma; Naveen K. Mehta (UTMS Journal of Economics, 2011)
The gamut of globalization is far reaching and yielding rich dividends to the business activities of developing countries like India. The impact of information and technology is clearly visible in augmenting the growth of business. The business houses are more prone to meet the deadline of their set objectives. The evolution of Business Process Outsourcing is an indication of enabling the organizations to nurture the available knowledge and utilizing the resources at the optimum level. In India, BPO as a career option is growing in leaps and bounds. It is very revealing that so far the youth of rural areas have not identifying BPO as a lucrative career option. The present research study was conducted on 200 youth aspirants belonging to suburban and rural areas of Madhya Pradesh, the second largest state of India in terms of area. The data were analyzed and interpreted and significant results were obtained.
Keywords: 330; BPO; career; dimensions; rural; youth; aspirants